(untitled) (Medicine Today, 2026)
Introduction with Objective: Postpartum mood disorders are the most common type of maternal morbidity following delivery and childbirth symbolizes for women a moment of extreme vulnerability to become mentally ill. The aim of this study was to assess the socio-demographic, hormonal and marital factors associated with postpartum depression. Materials & Methods: This Case control Study was carried out among 140 patients attending Outpatient and Inpatient department of Obstetrics and Gynecology of Dhaka Medical College and Hospital within the defined period from 1st January to 31st December 2022. The study was comprised of two groups, cases and controls. Patients attending outpatient and inpatient department of Obstetrics and Gynecology of Dhaka Medical College Hospital, who scored 10 or more than 10 in Edinburg Postpartum Depression Scale (EPDS) were considered as case group and who scored less than 10 in Edinburg Postpartum Depression Scale (EPDS) were considered as control group. All the data were compiled and sorted properly and the quantitative data was analyzed statistically by using Statistical Package for Social Science. Result: Most of the cases (n=62, 88.6%) had good understanding with their husbands in comparison of controls (n=69, 98.6%). Among the participants, who did not have good understanding with their husbands, number of cases 8(11.4%) were much higher than controls 1(1.4%) and the differences of the distributions were significant (p<0.05). Regarding the experience of domestic violence, most of the cases 54(77.1%) did not experience any domestic violence compared to 65(92.9%) of controls. 16(22.9%) cases had experienced domestic violence, compared to 5(7.1%) of controls. Participants who experienced domestic violence had higher rate of developing depression than controls and the differences of the distributions were statistically significant (p< 0.05). Conclusion: Post partum depression prevention appears to be possible and successful. Good understanding with the husband, support from family members and domestic violence are the important factor for PPD. Finally, there is an increasing effort to incorporate routine primary care for pregnant and postpartum women that includes mental health screening, treatment or referral, and follow-up care. Medicine Today 2026, Vol.38 (1): 10-13